INTEGRATED USE OF DIGITAL AND CLIL TECHNOLOGIES IN TEACHING FUTURE TEACHERS - Бегимбетова, Г.А.; Шекербекова, Ш.Т.; Ospankulov, Е. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2022)
The article discusses the problem of improving the concept of Content and Language Integrated Learning (CLIL). Currently, with the growing demands on graduates of pedagogical universities and the search for ways to prepare for multilingualism, it is becoming urgent to revise existing practices of teacher training. One of the solutions may be the formation of students' linguistic and information competence in CLIL classes, as an interconnected study of the content of the subject and a foreign language based on the use of Information and Communication Technologies (ICT). The purpose of the study is to test the effectiveness of using digital platforms in CLIL classes. Based on the results of the research conducted at AbaiKazNPU, an educational technology based on the active use of ICT tools, mixed learning and methodologically based on the principles of subject-language integrated learning CLIL, communicative-activity and competence approaches is proposed. The paper describes Internet tools, the use of which in CLIL classes will contribute not only to the familiarization or review of the studied information using audio or video materials, but also to the expansion and deepening of the content through the use of foreign-language web tools. Thus, fundamental computer skills developed on the basis of ICT tools can help students to master new material.